OVARIAN RESERVE AND ITS RELATION TO HORMONAL AND ULTRASOUND PARAMETERS IN INFERTILE WOMEN - Chakrabarti, Sudakshina; Sharma, Nidhi (International Journal of Psychosocial Rehabilitation, 2020)
Ovarian reserve testing has significant implications in fertility detection. These tests can predict a woman getting close to menopause which can be a sustained high level of Follicle stimulating hormone (FSH) in the blood or urine, along with a menstruation irregularity, is often used to confirm menopause, along with Antimullerian Hormone (AMH) levels which is commonly associated with antral and preantral follicle count.This study is to determine the relation between ovarian reproductive capacity with patient’s physical parameters like age, height, weight, BMI, hormonal parameters like basal Serum FSH, and AMH levels along with ultrasonographic parameter antral follicle count in basal scan to determine women with poor ovarian reserve in cases presenting with infertility in out patient department.(OPD)This study was conducted on 35 infertile patients presenting in the OPD. Basal levels of FSH, AMH was detected on day 2 or day 3 of their cycle along with basal transvaginal scan which was done on the same day .Age , height, weight of the women were noted along with their brief menstrual history. Correlation of the markers to age and each other was determined with statistical analysis. The parameters observed showed with increasing age there is a statistically positive correlation with FSH levels and negative correlation with Antimullerian hormone levels and Antral follicle Count. A very strong positive correlation is observed with antral follicle count and Day 2 serum AMH levels. A weak positive correlation was observed between menstrual cycle length and serum FSH levels. Thus it was seen that not only AMH , AFC is also are strong predictors of follicular reserve of the ovaries though they may not strongly determine the quality of the oocyte. Progressing age of a women do indicate declining ovarian reserve it still cannot be definitely said exactly at which age menopause will set in and when is the onset of decreased reproductive potential.